1988
DOI: 10.2307/3577123
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of Chromosome Aberrations during the Course of Radiation Therapy for Morbus Hodgkin

Abstract: In a patient with Morbus Hodgkin, structural aberrations of the chromosome type in peripheral lymphocytes were analyzed during radiation therapy (accumulated target dose 44.6 Gy: 22 fractions of 1.8 Gy each and 2 fractions of 2.5 Gy each at the end of the therapy). The blood was sampled about 5 min after a fraction and/or 24, 48, or 72 h thereafter. The frequency of dicentric chromosomes:acentric fragments:centric ring chromosomes is 37:14:1 throughout the therapy. Independent of the time of blood sampling aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
2
4
0
2
Order By: Relevance
“…The influence of treatment parameters on the yield of dicentrics and rings and on the distribution of these aberrations was also studied. As previously described, the yield of dicentrics and rings increased with the tumour dose for each patient but with substantial interindividual variability [24][25][26]. In agreement with other studies, a strong correlation between the size of irradiation field and the yield of chromosome aberrations was found [12,26,27].…”
Section: Discussionsupporting
confidence: 91%
“…The influence of treatment parameters on the yield of dicentrics and rings and on the distribution of these aberrations was also studied. As previously described, the yield of dicentrics and rings increased with the tumour dose for each patient but with substantial interindividual variability [24][25][26]. In agreement with other studies, a strong correlation between the size of irradiation field and the yield of chromosome aberrations was found [12,26,27].…”
Section: Discussionsupporting
confidence: 91%
“…A higher than expected frequency of dicentrics and micronuclei was also observed in lymphocytes of one of the control patients. It has been observed by different authors that the frequencies of aberrations and micronuclei in lymphocytes of patients undergoing radiotherapy are strongly variable between individuals (Obe et al, 1981;Diener et al, 1988). The reasons for this variability are not well understood.…”
Section: The Bialystok Accidentmentioning
confidence: 99%
“…Cytogenetic techniques, including the widely used analysis of chromosome aberrations [2,8,15,26,27,31,34,37,46] and the nowadays frequently used micronucleus test [3, 7, 9, 16, 23, 25, 28, 31, 34-36, 39, 42], are not only reliable indicators of damage to the cell genome in vivo and in vitro, but are also applicable for different and combined radiation qualities [45]. Our data agree with other authors mentioned above who demonstrated that RTX causes structural chromosome damage.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the CAT, a dose-dependent increase in the yield of CA frequency has been shown in RTX of patients at different sites [2,8,26,27]. It is a sensitive method for dose estimation but requires a very detailed analysis, which is very laborious and complex.…”
Section: Introductionmentioning
confidence: 99%